Evidence of Validity and Perspectives for Resilience Scales in Sport - Fonseca bicalho, Camila Cristina (2022)
The aim of this review was to identify the scales used to measure resilience in athletes and to assess their psychometric and semantic adaptations for the sporting context. An electronic search was conducted in six databases, for 2008-2019, and 43 articles were selected. The results showed 11 scales applied to evaluate resilience in athletes. In the semantic field, 11 factors were identified, conceptually different, that define the property of the psychological system for sports resilience. This study concluded that scales identified in literature to assess athletes’ resilience have been used indiscriminately. Only five had their psychometric properties evaluated for the sports context. Therefore, sport psychology lacks a sport-specific measure for resilience.